Hunting Billbug, Sphenophorus venatus vestitus Chittenden (Insecta: Coleoptera: Curculionidae) - Robert E. Woodruff (EDIS)
The hunting billbug, Sphenophorus venatus vestitus Chittenden, is a weevil that is also commonly known as the "zoysia billbug" in Florida, where it has been reported as a pest of various grasses, especially in nurseries. Billbug larva are often confused with white grubs, which is the name usually given to beetle larvae in the genus Phyllophaga, family Scarabaeidae.  This document is EENY-207 (originally published as DPI Entomology Circular 45), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2001.